BREEDING OF RICE VARIETIES WITH A HIGH CONTENT OF AMYLOSE - N. Yu. Bushman; V. N. Bruyako; E. А. Malyuchenko (Зерновое хозяйство России, 2018)
There are different appraisal criteria for the reference of rice varieties to the group of cultivars with high quality. In India, Bangladesh and the Philippines the people prefer the high amylose varieties which are boiled soft. The starch properties are the key factor for the nutritional and culinary qualities of the cooked rice, and the quantity of proteins and their amino acid composition affect its nutritional value. The starch in the grain kernels is the 6-carbon sugars, polymerized into the granules of starch endosperm. One part of spare starch in grains presents the direct chains of amylose; the other part is the amylopectin with the branched molecular structure. The starch of the gluten or waxy rice completely consists of the amylopectin. The groats of the varieties with high content of amylose (more than 25%) isn’t boiled soft and can be used for pilaf and other cuisines where it’s important to preserve the integrity of a kernel and its attractive appearance. In Russia we cultivated only low-amylose varieties with its content of 1519%, but the last time there is a necessity to develop domestic varieties with the amylose content more than 20% and the varieties with higher content of gluten. The samples of the sub type indica of foreign breeding have been involved in the hybridization as the donors of the trait. Despite the high content of bare kernels of the intersubspecific hybrids, the second generation of the hybrids produces the highly productive and more promising plants for further hybridization. The analysis of the breeding material showed the possibility to grow the varieties with the long and large kernels with the different rate of maturity. During the control trial and competitive variety testing we selected the samples with the content of amylose more than 20%.